2013
DOI: 10.2753/mer1052-8008230304
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Classroom Effectiveness Through Social Networking Tools

Abstract: Reaching students hinges on understanding them and how they communicate. Marketing education, like education in other disciplines, must fit into the lives of the students. While education must challenge and transform students, it should also include recognition of the way that they think and communicate. Thus, the choices that we as instructors make in the classroom have both direct and indirect effects. Our decisions concerning teaching pedagogy lead to changes in the way that students work together and learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the past, edutainment was mostly examined in the context of education and was examined through experiential learning and in‐class games (Bonwell & Eison, ). This stream of research often focused on the impact of edutainment on communication, persuasion, and learning outcomes (Haytko, ; Kurthakoti, Boostrom, Summey, & Campbell, ; Singhal & Rogers, ). This study extends the blended use of educational and entertainment content to a travel consumption setting.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, edutainment was mostly examined in the context of education and was examined through experiential learning and in‐class games (Bonwell & Eison, ). This stream of research often focused on the impact of edutainment on communication, persuasion, and learning outcomes (Haytko, ; Kurthakoti, Boostrom, Summey, & Campbell, ; Singhal & Rogers, ). This study extends the blended use of educational and entertainment content to a travel consumption setting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Abney et al (2019) emphasised the importance of tools such as Twitter for stimulating debate between students and teachers in marketing learning. Kurthakoti et al (2013) verified that using social networks increases the performance of work teams, while McCorkle and McCorkle (2012) concluded that LinkedIn helps individuals to acquire transversal skills, such as social communication and creativity. Social networks improve the quality of the relationships that educational institutions establish with students, because they enhance the effectiveness of communication strategies (Clark et al, 2017;Peruta and Shields, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…This study used a directed qualitative analytic approach and a tool of analysis that was conceptually informed by edutainment and narrative transportation theory (Green and Brock, 2000). Findings from the research aim to make contribution to a body ‘of research [that is] often focused on the impact of edutainment on communication, persuasion, and learning outcomes (Haytko, 2006; Kurthakoti et al, 2013; Singhal and Rogers, 2002)’. (Chan, 2019: 200).…”
Section: Discussionmentioning
confidence: 99%